Molecular characteristics, clonal transmission, and risk factors of Clostridioides difficile among hospitalized patients in a tertiary hospital in Ningbo, China - Hu, Liqing; Lin, Shan; Zhang, Meng; Cai, Mengting; Shen, Yuhang; Zeng, Peng; Song, Xiaojun; Bian, Qiao; Gu, Jina; Luo, Yun; Chen, Yu; Jin, Dazhi (Frontiers in Microbiology, 2024)
BackgroundNosocomial transmission of Clostridioides difficile infection (CDI) has been documented in Ningbo, China. However, data on molecular characteristics, clonal transmission, and risk factors of CDI in this region remain limited.MethodsA cross-sectional study enrolled hospitalized patients with diarrhea during September to November 2021. Stool samples from all patients were tested for C. difficile, and isolated strains underwent toxin gene identification, genotyping, and antibiotic susceptibility testing. Whole-genome sequencing and epidemiological variables were analyzed in patients infected with C. difficile strains of the same sequence types (STs) to identify nosocomial transmission and risk factors for CDI.ResultsOf the 907 investigated patients, 115 (12.7%) had microbiologically proven CDI, as their diarrhea was associated with toxigenic C. difficile strains, which comprised 106 A+B+CDT−, 3 A−B+CDT−, and 6 A+B+CDT+. Predominant genotypes (ST2, ST3, ST35, and ST54) exhibited distinct antibiotic resistance patterns. ST54 strains showed higher resistance to erythromycin (100%) but lower resistance to moxifloxacin (18.2%) and gatifloxacin (18.2%) (χ2 = 10.24–16.65, p < 0.05). ST35 strains exhibited higher resistance to ciprofloxacin (66.7%) and tetracycline (33.3%) than other STs (χ2 = 13.30–20.19, p < 0.05). Genomic and epidemiological analysis revealed two nosocomial clonal transmission events caused by 5 ST35 strains (with ≤2 single nucleotide polymorphism differences), elucidating clonal transmission among different floors and buildings within the hospital. Prolonged hospitalization (> 10 days) (odds ratio [95% confidence interval], 1.76 [1.05–2.93]) and penicillin-class antibiotics (1.69 [1.11–2.58]) were risk factors for CDI, with the latter being an independent risk factor (1.57 [1.02–2.42]). For C. difficile ST35 infection, intensive care unit (12.00 [2.77–52.05]) and neurology departments (8.08 [1.46–44.65]) admissions were risk factors, with the latter as an independent risk factor (1.56 [1.01–2.40]).ConclusionMultiple C. difficile genotypes with varied antibiotic resistance patterns circulated in Ningbo, with ST35 causing nosocomial clonal transmission among different floors and buildings within the hospital. These findings and the identified risk factors necessitate enhanced surveillance and infection control in the region.